IMPLEMENTASI MANAJEMEN STRATEGIS DAN STRATEGI PRICING MENGGUNAKAN ANALISA S.W.O.T DI STIE INDONESIA BANKING SCHOOL - Lediana Sufina; Harley Bayu; Rudy Perdana; Muhammad Ariel Budiman; Muhammad Rafly Tirtagiri (Journal of Accounting, Management and Islamic Economics, 2025)
The phenomenon of our case study is the low number of students who apply to STIE Indonesia Banking School, with this our aim is to find the source of the problem through managerial insight and SWOT analysis to try to find a solution. In this case study we use a descriptive qualitative technique. From the results of this study, we found that there was an indication of a decline in new student admissions at IBS caused by the following factors: first, IBS competitors did aggressive marketing and dared to take the first step in attracting prospective students. Both tuition fees are quite large from the IBS side, which makes enthusiasts look for alternatives to colleges that are more affordable. The three Competitor alumni are quite well known and easy to find anywhere which makes the competitor's campus name bigger. Once some insights have been released and our research has reached its end, we therefore present some conclusions from our findings. The management strategy in marketing is very necessary, especially since IBS already has a name in BI and commercial banks which makes IBS easily famous. This must be used by marketing to aggressively market educational service products not only at exhibitions, but outside such as stands in shopping centers such as malls, digital marketing, and others. IBS's transition strategy from product differentiation to cost leadership is quite slow and requires IBS to be prepared for all eventualities. We hope that this research is useful for further researchers, there must be bresearchers who are able to make more comprehensive research using quantitative methods to uncover some research gaps that we have not found with a wider variables.